Cocriação de valor do cliente associada ao alinhamento estratégico entre negócio e projetos de Tecnologia da Informação - Chagas Montenegro Duarte, Cássio (Revista Vozes dos Vales: Publicações Acadêmicas, 2015)
The main objective of this work is to establish an association between value co-creation and Information Technology (IT) project management. In addition, it aims to contribute to a deeper understanding of project management techniques. The study was conducted using a qualitative approach, with a literature review complemented by empirical research aimed at observing the phenomenon in order to discover important aspects related to the main question. The article proposes the use of co-creation as a tool that allows clients to expand the possibilities of using project requirements by integrating them with their own resources, skills, and competencies, in order to foster other complementary goods or services generated from derivative projects.
Keywords: Strategic Alignment; Project Management; Co-creation